Epidemiological evidence of increased waist circumference, but not body mass index, associated with impaired baroreflex sensitivity. Issue 2 (March 2020) - Li, Chung-Hao; Sun, Zih-Jie; Lu, Feng-Hwa; Chou, Yu-Tsung; Yang, Yi-Ching; Chang, Chih-Jen; Wu, Jin-Shang
Abstract: Although an inverse relationship between body mass index (BMI) and baroreflex sensitivity (BRS) was found, the effect of waist circumference (WC) on BRS is still inconclusive. The contradictory results of previous studies may be related to the heterogeneity and relatively small sample size of the subjects examined. The aim of this population-based study was to investigate whether the influence of increased WC is more detrimental to BRS than BMI. A total of 760 community dwellers were recruited and they were classified into Q1 (n = 189), Q2 (n = 183), Q3 (n = 192) and Q4 (n = 196) groups, based on WC quartiles. Spontaneous BRS was determined by spectral α coefficient method. Valsalva ratio was the longest RR interval after release of Valsalva maneuver divided by the shortest RR interval during maneuver. Cardiac autonomic function was calculated by power spectrum of heart rate in low and high frequency (LF, 0.04–0.15 Hz; HF, 0.15–0.40 Hz), and LF/HF ratio in supine position for five minutes. There were significant differences in spontaneous BRS and Valsalva ratio among different WC groups. In multivariate analysis, obesity was inversely associated with spontaneous BRS and Valsalva ratio. However, these inverse relationships became insignificant after further adjustment for WC quartiles. In contrast, Q4 vs. Q1, Q3 vs. Q1 and Q2 vs. Q1 of WC were inversely related to spontaneous BRS. Q4 vs. Q1 and Q3 vs. Q1 of WC were negatively associated with the Valsalva ratio. In conclusion, increased and even high-normal WC had a stronger adverse effect on BRS than BMI, independent of cardio-metabolic risk factors.